An in situ study of thermal crystallization of amorphous calcium phosphates. Issue 39 (4th October 2022) - Degli Esposti, Lorenzo; Fosca, Marco; Canizares, Aurélien; Del Campo, Leire; Ortenzi, Marco; Adamiano, Alessio; Rau, Julietta V.; Iafisco, Michele
Abstract : Time-resolved energy dispersive X-ray diffraction and infrared spectroscopy were employed to study in situ the thermal crystallization of amorphous calcium phosphate nanoparticles. Abstract : The heat-induced crystallization of amorphous calcium phosphate (ACP) is an intriguing process not yet well comprehended. This is because most of the works on this topic are based on ex situ studies where the materials are characterized after the heat and cooldown cycles, thus missing transient structural changes. Here, we used time-resolved energy dispersive X-ray diffraction and infrared spectroscopy to study, for the first time, the thermal crystallization of ACP in situ . The thermal crystallization of two kinds of citrate-stabilized carbonated ACP was studied, as they are promising materials for the preparation of advanced bioceramics. The behavior of these samples was compared to that of two citrate-free ACPs, either doped or non-doped with carbonate ions. Our results evinced that several phenomena occur during ACP thermal annealing. Before crystallization, all ACP samples undergo a decrease in the short-range order process, followed by several internal reorganizations. We have assessed that differently from carbonate-free ACP, carbonated ACPs with and without citrate directly crystallize into a biomimetic poorly crystalline carbonated hydroxyapatite. Citrate-stabilized ACPs in comparison to citrate-free ACPs have a faster hydroxyapatite formation kinetics, which is due to their higher specific surface area. This work reveals the necessity and the potentialities of using in situ techniques to effectively probe complex processes such as the heat-induced crystallization of ACPs.